Multimodal discontinuous reaction in Ni-Fe-Cr-Al alloy. (15th March 2021) - Lech, Sebastian; Polkowski, Wojciech; Polkowska, Adelajda; Cempura, Grzegorz; Kruk, Adam
Abstract: Ni-Fe-Cr-Al alloy has been subjected to 2 hours aging treatment between 600-900°C, which influenced the mechanical properties and resulted in discontinuous precipitation at the grain boundaries. In this study, SEM, TEM and STEM-EDXS were applied to explore the relationship between the occurring grain boundary precipitation phenomena and mechanical behavior. Within the discontinuous precipitation zone, three different phases were recognized, namely γ solid solution with lamellar M23 C6 carbides and elongated γ' precipitates at the reaction front. Coherency of the discontinuous precipitates was identified as they have shown a cube-on-cube orientation relationship. Furthermore, the development of multiple discontinuous reactions was discussed. Graphical abstract: Image, graphical abstract